ПОМОГИТЕ РЕШИИИИТЬ!!!!

1) (3Х-2)^2 - (х+6) (х-6)= 4х(2х+3)+43
2) (5-х)^2 - (3-2х) (3+2х) = 2,5 (7-4х)+13½

2

Ответы и объяснения

2013-01-03T10:31:14+00:00

1)  

(3х - 2)^2 – (х^2 - 36) = 8х^2 + 12х + 43

9х^2 – 12х + 4 – х^2 + 36 = 8х^2 + 12х + 43

24х = -3

Х= - 0,125

 

2) в конце  13½  это как 13,5 или 13 в степени  ½ ?

  • IZUBR
  • светило науки
2013-01-03T10:32:46+00:00

 (3x-2)^2 -(x+6) (x-6)= 4x*(2x+3)+43;\\ 9x^2-12x+4-x^2-6x+6x+36=8x^2+12x+43;\\ 9x^2-x^2-8x^2-12x-6x+6x-12x+36+4-43=0;\\ -24x^2=3;\\ x=-1/8;\\ x=-0,125.

(5-x)^2 - (3-2x) (3+2x) = 2,5 (7-4x)+13*1/2;\\ 25-10x+x^2-9-6x+6x+4x^2=17,5-10x+6,5;\\ 5x^2+25-9-24=0;\\ 5x^2=8;\\ x=+/-\sqrt{8/5};\\ x1=\sqrt{8/5}\\ x2=-\sqrt{8/5}\\

Вот так.

Либо второе решается так: (Если 13,5).

(5-x)^2 - (3-2x) (3+2x) = 2,5 (7-4x)+13,5;\\ 25-10x+x^2-9-6x+6x+4x^2=17,5-10x+13,5;\\ 5x^2+16=31;\\ 5x^2=15;\\ x^2=3;\\ x=+/-\sqrt{3};\\